Writing Without Peter: Reflections on Peter Elbow and His Legacy: Peter Elbow the Philosopher - Irene Papoulis (Journal of the Assembly for Expanded Perspectives on Learning, 2025)
On the occasion of Peter Elbow’s passing, we read many tributes and praises commemorating him and the foundational contributions he made to the multi-faceted field of writing studies. But as we know, even as Peter’s ideas were lauded and embraced, they were also questioned by many, including other renowned members of our profession.